Hubungan Penggunaan Game Online Dengan Perilaku Agresif Verbal Pada Remaja Di Desa Bumisari Kecamatan Bojongsari Kabupaten Purbalingga - Puput Yulianingrum; Wasis Eko Kurniawan; Indri Heri Susanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Today's youth cannot be separated from gadgets. Gadgets are not only used as a communication tool, but tend to be used to carry out online activities, one of which is online games. The environment of the game is based on violent plot activity, aggression and even gender intimidation. Aggressive actions taken by children as a result of playing games can appear because they lack or even do not care about real life. The study aims to determine the relationship between the use of online games and aggressive verbal behavior in adolescents in Bumisari Village, Bojongsari District, Purbalingga Regency. The sampling technique with a total sampling of 89 teenagers. Data collection was carried out using a questionnaire on the use of online games and aggressive behavior. The results showed that there was a relationship between the use of online games and verbal aggressive behavior in adolescents in Bumisari Village, Bojongsari District, Purbalingga Regency. The results of the correlation test using the Spearman Rho test showed a value of p = 0.001 or p = ≤ 0.05. The correlation value (r) was obtained r = 0.349 which indicates a moderate (moderate) correlation strength between the use of online games and verbal aggressive behavior. The correlation value of r = 0.349 shows a positive relationship, which means that the higher the intensity of using online games, the higher the aggressive verbal behavior will be. The conclusion is that online games are related to verbal aggressive behavior in adolescents